Primarni sklerozantni holangitis - Dajčman, Davorin (Medicinski razgledi, 1999)
The aetiology and pathogenesis of the inflammatory and fibrotic bile duct lesions characteristic of primary sclerosing cholangitis is unknown, but several lines evidence support connection that genetic and immunologic factorsare involved. Disease is characterised by ongoing inflammation, destruction and fibrosis of intrahepatic and extrahepatic bile duct. Irreversible damage to the bile ducts leads cholestasis, cirrhosis and liver failure with premature death unless liver transplantation is performed. It is frequently associated with inflammatory bowel disease, usually ulcerative colbis. There is no satisfactory medical therapy for patients with primary sclerosing cholangitis. Lacking a specific remedy the goal of treatment is controlling inflammation and infection and to prevent scaring. Liver transplantation is treatment of choice in advanced liver disease.
Keywords: Cholangitis, sclerosing; jetra; diagnostika; žolčni vodi; bolezni; disease; vnetja; zdravljenje; therapy